Is the hypoxic ventilatory response driven by blood oxygen concentration? - Milsom, W. K.; Wang, T. (The Journal of Experimental Biology, 2017)
Bill Milsom and TobiasWang discuss the impact of Mogens Glass, Robert Boutilier and Norbert Heisler`s classic paper `Ventilatory control of arterial PO2 in the turtle Chrysemys picta bellii: Effects of temperature and hypoxia`, published in Journal of Comparative Physiology in 1983.